2011
DOI: 10.1002/app.35264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybridization and compatibilization on the mechanical properties of recycled polypropylene‐hemp composites

Abstract: Hemp fibers and particles, with different sizes and contents, were used to make hybrid composites based on recycled polypropylene (PP). In particular, the effect of maleated polypropylene (MAPP) addition on the morphology and mechanical properties is reported. The results show that better adhesion is obtained with MAPP addition. In general, fiber content and size had a substantial effect on the tensile, flexural, torsion, and impact properties of the resulting composites. Although, adding MAPP to the samples i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…As expected, density increased with total fiber content (Table 1), but particle size ratio had no significant effect. These results are in agreement with those reported by Ramezani-Kakroodi et al [11].…”
Section: Densitysupporting
confidence: 95%
“…As expected, density increased with total fiber content (Table 1), but particle size ratio had no significant effect. These results are in agreement with those reported by Ramezani-Kakroodi et al [11].…”
Section: Densitysupporting
confidence: 95%
“…As one kind of polymer based composites, wood/polymer composites (WPCs) have emerged as both constructive and decorative materials. They are rarely used as load‐bearing materials due to their inferior mechanical strength compared with natural wood . Using inorganic particles like silica, MMT, titanium dioxide, and calcium carbonate is an alternative to enhance WPC's thermal properties, mechanical properties, and water resistance.…”
Section: Introductionmentioning
confidence: 99%
“…They are rarely used as load-bearing materials due to their inferior mechanical strength compared with natural wood. [16,17] Using inorganic particles like silica, MMT, titanium dioxide, and calcium carbonate is an alternative to enhance WPC's thermal properties, mechanical properties, and water resistance. Among these particles, silica and MMT have been widely used as fillers in the WPC frication.…”
mentioning
confidence: 99%
“…One important aspect of hybrid composites is that synergistic effects can be produced between the different reinforcement used leading to properties much higher than expected, especially when using the simple linear rule of hybrid mixtures (RoHM). [5,6] For example, Ramezani Kakroodi et al [7] combined different concentration of hemp fibers in polypropylene and observed that for a total hemp content of 20% wt., an optimum tensile modulus of 518 MPa was obtained for a 20/80 (weight ratio) of short/long fibers compared to a composite having 100% short fibers (425 MPa) or 100% long fibers (472 MPa). The effect was also seen at 30% wt.…”
Section: Introductionmentioning
confidence: 99%
“…Tensile modulus as a function of composition for hemp fibers (h) in a polypropylene (PP) matrix. The first and second numbers report the total fiber content (wt.%) and the amount of long fibers (%) compared to short ones [7] 2 Modeling…”
Section: Introductionmentioning
confidence: 99%